Upaya Meningkatkan Hasil Belajar Matematika Melalui Penerapan Model Pembelajaran Berbasis Masalah - Butar Butar, Toni (JURNAL GLOBAL EDUKASI, 2020)
Abstract: The root of the problem in this study is poor student learning outcomes. Toovercome this problem, this study applies a problem-based learning model. This researchis a classroom action research, with the research subjects of class IX-2 SMP Negeri 3Muara, totaling 32 people. This research's object is student learning outcomes through theapplication of problem-based learning on quadratic function material in class IX-2 ofSMP Negeri 3 Muara. The instrument used was a test. The test consists of a pre-test and apost-test, each of which consists of 5 items. In the first cycle, the number of students whoobtained the "complete" category was 21 people, and the percentage of classicalcompleteness was 65.60%. In the second cycle, the number of students who obtained the"complete" category was 28 people, and the percentage of classical completeness was87.50%. From the results of the actions in cycle I and cycle II, it was concluded that therewas an increase in student learning outcomes in the Quadratic Functions material throughthe application of the Problem-Based learning model in class IX of SMP Negeri 3 Muarain the 2019/2020 academic year.Keyword: problem-based; quadratic functionAbstrak: Akar masalah dalam penelitian ini adalah rendahnya hasil belajar siswa. Untukmengatasi masalah tersebut, pada penelitian ini diterapkan model pembelajaran berbasismasalah. Penelitian ini merupakan penelitian tindakan kelas, dengan subjek penelitiansiswa kelas IX-2 SMP Negeri 3 Muara yang berjumlah 32 orang. Objek dalam penelitianini adalah hasil belajar siswa melalui penerapan pembelajaran berbasis masalah padamateri fungsi kuadrat di kelas IX-2 SMP Negeri 3 Muara. Instrumen yang digunakanadalah tes. Tes terdiri atas tes awal dan tes akhir (post test), yang masing-masingberjumlah 5 butir soal. Pada siklus I jumlah siswa yang memperoleh kategori â€œtuntasâ€sebanyak 21 orang dan persentase ketuntasan klasikal sebesar 65,60%. Pada siklus IIjumlah siswa yang memperoleh kategori â€œtuntasâ€ sebanyak 28 orang dan persentaseketuntasan klasikal sebesar 87,50%. Dari hasil tindakan pada siklus I dan siklus II makadisimpulkan ada peningkatkan hasil belajar siswa pada materi Fungsi Kuadrat melaluipenerapan model pembelajaran Berbasis Masalah di kelas IX SMP Negeri 3 Muara tahunpelajaran 2019/2020.Kata kunci: berbasis masalah; fungsi kuadrat